1996
DOI: 10.1524/ract.1996.74.special-issue.99
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Curium(III) in Concentrated Electrolyte Solutions : Formation of Sulfate Complexes in NaCl/Na2SO4 Solutions

Abstract: The formation of sulfate complexes of Curium in aqueous solutions is studied by time resolved laser fluorescence spectroscopy (TRLFS) at 25 °C. The species Cm", Cm(S0 4 )\ Cm(S0 4 )ï and Cm(S0 4 )5~ are quantified spectroscopically in the trace concentration range by peak deconvolution of fluorescence emission spectra. The complex formation equilibria are measured in NaCl/ Na 2 S0 4 solutions of constant ionic strength (3 molai) as a function of the sulfate concentration. The stability constants of Cm(S0 4 ) +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 8 publications
1
27
0
Order By: Relevance
“…OH vibration of co-ordinated H 2 O molecules. The experimental lifetime for the Eu 3+ aquo ion is 110 ± 5 µs in water [15][16][17][18][19]. A linear correlation is observed between the decay rate and the number of H 2 O molecules in the first co-ordination sphere of Eu(III), where a lifetime of 110 µs, corresponds to 9, and 1725 µs to zero H 2 O molecules [17].…”
Section: Lifetime (Fluorescence Decay) Of Eu(iii) Emissionmentioning
confidence: 90%
See 1 more Smart Citation
“…OH vibration of co-ordinated H 2 O molecules. The experimental lifetime for the Eu 3+ aquo ion is 110 ± 5 µs in water [15][16][17][18][19]. A linear correlation is observed between the decay rate and the number of H 2 O molecules in the first co-ordination sphere of Eu(III), where a lifetime of 110 µs, corresponds to 9, and 1725 µs to zero H 2 O molecules [17].…”
Section: Lifetime (Fluorescence Decay) Of Eu(iii) Emissionmentioning
confidence: 90%
“…TRLFS measurements were performed by using a pulsed Nd:YAG pumped dye laser system (Continuum, Powerlite 9030, ND 6000) and by using a flash lamp pumped Ti:sapphire laser (Elight, Titania). Details on the experimental set-up are given elsewhere [11][12][13][14][15][16]. Laser pulse energy of at most 4 mJ was controlled by a photodiode.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…5b), log K 0 1:1 = 6.21, is smaller than the complexation with carbonate (log K 0 1:1 = 8.30; [19]) and clearly stronger than complexation with sulfate (log K 0 1:1 = 3.28; [19]). The strength of Cm(III) complexes with divalent complexing inorganic ligands thus follows the line: CO 3 2− > HPO 4 2− SO 4 2− . The results of our study showed that HPO 4 2− belongs to the strong inorganic complexing ligands.…”
Section: Thermodynamic Speciation and Strength Of The Complexesmentioning
confidence: 95%
“…Using ion exchange, an indirect speciation technique, stability constants log K of Ln/AnH 2 PO 4 2+ species between 1.52 and 1.69 at ionic strengths of 0.2 and 0.5 M were determined. Later many speciation studies of Cm(III) in several of inorganic systems, e.g., silicate [2]; sulfate [3]; dihydrogenphosphate [4], hydroxide [5][6][7]; chloride [5,6]; carbonate [5,6] and nitrate [8] applied TRLFS. All these investigations demonstrated that the characteristic luminescence emission band of Cm 3+ at 593.7 ± 0.1 nm is sensitive to changes in its first coordination sphere.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of Cm(in) with main natural inorganic ligands Cl", SOJ", and COi~ was investigated and appropriate thermodynamic models were developed which are valid from low to high ionic strength [1][2][3][4], The goal of the present contribution is to develop a thermodynamic model describing the chemical behaviour of trivalent actinides in high Chloride concentrations. Recently published experimental data for the Chloride complexation of Cm(III) in CaClj solutions, determined by time-resolved laser fluorescence spectroscopy (TRLFS) [1], are used to parameterize the ion interaction (Pitzer) approach.…”
Section: Introductionmentioning
confidence: 99%